Literacies: a bilingual perspective for deaf learners - Teixeira, Aline Thomaz de Oliveira; Moraes, Fernanda Beatriz Caricari (The ESPecialist, 2024)
This paper presents the elaboration of Visual Literacy strategies in the education of deaf students and aims to show suggestions of materials to compose a multimodal reading room, with a bilingual perspective, entitled “Literacy Space”. With the proposal to develop an online coexistence space, which brings together examples of Deaf Literature from different textual genres, with a Bakhtinian approach to discursive genres, and artistic representations, which express their experiences in these media, among these. The work brings together two major themes, literacy anchored in the perspective of multiliteracies (NLP, 1996) and teaching Portuguese as a second language for deaf people. It is expected that this online literacy proposal will contribute to the learning of written Portuguese and Libras of the deaf learner.